Bioprocessing technology for production of biopharmaceuticals and bioproducts - Komives, Claire; Zhou, Weichang, 1963- (Wiley series in biotechnology and bioengineering., 2019)
"Written for industrial and academic researchers and development scientists in the life sciences industry, Bioprocessing Technology for Production of Biopharmaceuticals and Bioproducts is a guide to the tools, approaches, and useful developments in bioprocessing. This important guide: Summarizes state-of-the-art bioprocessing methods and reviews applications in life science industries Includes illustrative case studies that review six milestone bio-products Discusses a wide selection of host strain types and disruptive bioprocess technologies"--Provided by publisher